Airborne Seeker Application in Three Dimensional Formation Flight of UAVs - M. B Menhaj; M. A. Dehghani1; M. Azimi (AUT Journal of Electrical Engineering, 2018)
This paper deals with the leader-follower formation control problem while communication constraint in data transmitting is considered. From a practical point of view, we study the case in which unmanned vehicles are subject to the limited sensing, and communication is of a particular interest. A three-dimensional formation flight of multi-unmanned aerial vehicles with leader-follower configuration is investigated. We assume that the follower is equipped with an airborne seeker to measure the relative kinematic parameters with respect to the leader. Considering practical measurements of the airborne seeker, the kinematics of the leader-follower system is derived and by employing a cascade loop controller, the relative angle and the relative range are regulated to reach at the desired formation. Moreover, by modeling the seeker mechanism, the effect of the seeker dynamics and sensor measurement noise on the performance of the proposed formation control scheme are studied. Simulation results verify the effectiveness of the proposed leader-follower formation control structure